Effect of ultrasonic ecxitation on the ultimate tensili strength of glass ionomer cements after different water storage times - Azevedo, Elcilaine [UNESP]; Coldebella, Carmen Regina; Souza, Juliana F. [UNESP]; Zuanon, Angela Cristina Cilense [UNESP] (My University, 2012)
The application of ultrasound waves with a conventional dental ultrasonic scaler on glass ionomer cements surface accelerated initial setting reaction and improved the mechanical properties. Objective: This study evaluated the ultimate tensile strength of glass ionomer cements after ultrasonic excitation and different water storage times. Material and method: Twelve specimens of each material (Fuji IX GP, Ketac Molar Easymix and Vitremer) were prepared, and six of each received a 30-second ultrasound application during initial setting of the cements. After storage of the 24 hours or 30 days, the specimens were sectioned into stick to microtensile testing and the mean ultimate tensile strength values were submitted to Welch’s ANOVA and Tamhane’s test. Result: The results showed that the Vitremer presented the highest mean tensile strength. The chemically set Fuji IX GP presented significantly higher mean tensile strength after 30 days than after 24 hours of storage (p < 0.05). At 24 hours, the ultrasonically set Fuji IX GP presented significantly higher mean tensile strength than their counterparts set under standard conditions (p < 0.05). Conclusion: Treatment with ultrasound increased the tensile strength of Fuji IX GP in the early period of maturation.

A aplicação de ondas ultrassônicas no cimento de ionômero de vidro acelera a velocidade da reação de presa inicial e melhora as propriedades mecânicas do material. Objetivo: Este estudo avaliou a resistência máxima à tração de cimentos de ionômero de vidro após excitação ultrassônica e tempos diferentes de armazenamento de água. Material e método: Doze corpos de prova de cada material (Fuji IX GP, Ketac Molar Easymix e Vitremer) foram preparados e seis receberam aplicação de ultrassom por 30 segundos durante a reação de presa inicial. Após armazenamento de 24 horas ou 30 dias, foram seccionados em espécimes na forma de palito e submetidos ao teste de microtração. Os valores médios de resistência à tração foram avaliados pela análise de variância e teste de Tamhane com correção de Welch. Resultado: O cimento Vitremer apresentou as maiores médias de resistência à tração. Foi observado que o tratamento com ultrassom aumentou a resistência do cimento Fuji IX GP com 24 horas de armazenamento e esta se manteve após 30 dias de armazenamento (p < 0,05). No grupo controle, Fuji IX GP com 30 dias armazenamento apresentou resistência à tração maior que o armazenamento de 24 horas (p < 0,05). Conclusão: O tratamento com ultrassom aumentou a resistência à tração do Fuji IX GP, no período inicial de sua maturação.
Efeito da excitação ultrassônica na resistência máxima à tração de cimentos de ionômero de vidro, após diferentes períodos de armazenamento
Keywords: Glass ionomer cements; Ultrasonics; Tensile strength; Cimentos de ionômero de vidro; Ultrassom; Resistência à tração